Cyclosporin a disrupts notch signaling and vascular lumen maintenance. - Raghav Pandey; Mark A Botros; Benjamin A Nacev; Allan R Albig (PLoS ONE, 2015)
Cyclosporin A (CSA) suppresses immune function by blocking the cyclophilin A and calcineurin/NFAT signaling pathways. In addition to immunosuppression, CSA has also been shown to have a wide range of effects in the cardiovascular system including disruption of heart valve development, smooth muscle cell proliferation, and angiogenesis inhibition. Circumstantial evidence has suggested that CSA might control Notch signaling which is also a potent regulator of cardiovascular function. Therefore, the goal of this project was to determine if CSA controls Notch and to dissect the molecular mechanism(s) by which CSA impacts cardiovascular homeostasis. We found that CSA blocked JAG1, but not Dll4 mediated Notch1 NICD cleavage in transfected 293T cells and decreased Notch signaling in zebrafish embryos. CSA suppression of Notch was linked to cyclophilin A but not calcineurin/NFAT inhibition since N-MeVal-4-CsA but not FK506 decreased Notch1 NICD cleavage. To examine the effect of CSA on vascular development and function, double transgenic Fli1-GFP/Gata1-RFP zebrafish embryos were treated with CSA and monitored for vasculogenesis, angiogenesis, and overall cardiovascular function. Vascular patterning was not obviously impacted by CSA treatment and contrary to the anti-angiogenic activity ascribed to CSA, angiogenic sprouting of ISV vessels was normal in CSA treated embryos. Most strikingly, CSA treated embryos exhibited a progressive decline in blood flow that was associated with eventual collapse of vascular luminal structures. Vascular collapse in zebrafish embryos was partially rescued by global Notch inhibition with DAPT suggesting that disruption of normal Notch signaling by CSA may be linked to vascular collapse. However, multiple signaling pathways likely cause the vascular collapse phenotype since both cyclophilin A and calcineurin/NFAT were required for normal vascular function. Collectively, these results show that CSA is a novel inhibitor of Notch signaling and vascular function in zebrafish embryos.